Circular RNA microarray expression profile in 3, 4‐benzopyrene/angiotensin II‐induced abdominal aortic aneurysm in mice. Issue 6 (4th January 2019) - Wang, Jiaoni; Sun, Huankun; Zhou, Yingying; Huang, Kaiyu; Que, Jiaqun; Peng, Yangpei; Wang, Jinsheng; Lin, Cong; Xue, Yangjing; Ji, Kangting
Abstract: Abdominal aortic aneurysm (AAA) is an unpredictable but lethal disease that poses a therapeutic dilemma. Circular RNAs (circRNAs), whose functional roles as transcriptional regulators and microRNA (miRNA) sponges have been shown in former studies, are potential biomarkers for many diseases. AAA in male C57BL/6 J mice was induced by coadministration of angiotensin II (Ang II) and 3, 4‐benzopyrene (BaP). The circRNA expression profiling was performed using two samples from the control group and two samples from the AAA group. Quantitative real‐time polymerase chain reaction (qRT‐PCR) was used to confirm the reliability of the microarray results. Among the 14 236 detected circRNAs, 413 showed obvious expression changes (fold change ≥ 2; P  < 0.05) between the BaP/Ang II‐induced AAA group and control group. Of the 413 that showed significant changes, 271 were upregulated, while the other 142 were downregulated. The expression levels of 10 circRNAs were validated by qRT‐PCR. The interactions of the differentially expressed circRNAs with miRNAs were predicted. Immunofluorescence showed prominent vascular smooth muscle cell apoptosis in abdominal aortic tissues in the BaP/Ang II group. Furthermore, a circRNA‐miRNA coexpression network based on six apoptosis‐related circRNAs was built. The genes regulated by the network mapped to several pathways, including apoptosis, the IL‐17 signaling pathway, and vascular endothelial growth factor signaling pathway, all of which are related to AAA formation. This study performed circRNA expression profiling in AAA and the results specifically predicted the regulatory role of circRNAs in AAA pathogenesis. Abstract : Differentially expressed circular RNAs (circRNA) in BaP/Ang II‐induced mouse abdominal aortic aneurysm (AAA) were detected compared with the control group. Vascular smooth cell apoptosis is a key pathology in AAA. Six apoptosis‐related circRNAs were used to build a circRNA‐miRNA coexpression network for further revealing the knowledge of their biological functions.